Pengaruh Kombinasi Relaksasi Benson Dan Murottal Al-Qur’An Terhadap Penurunan Tekanan Darah Dan Kecemasan Pada Penderita Hipertensi - Tifany Hayuning Ratri (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2024)
Anxiety is a psychological factor that can affect hypertension. The non-pharmacological management for hypertensive patients is a combination of benson relaxation and murottal Al-Qur'an. The aim study was to determine the effect of a combination of benson relaxation and murottal Al-Qur'an on reducing blood pressure and anxiety in hypertensive patients. The research quasi-experimental design a pretest and posttest control group design. The experimental group in this study was the group that received combination therapy of benson relaxation and murottal Al-Qur'an and treatment from the puskesmas, while the control group was the group that received treatment from the puskesmas. Wilcoxon blood pressure pretest and posttest p=0.000 (p<0.05) there is a change in blood pressure in patients with hypertension. Mc Nemar on anxiety pretest and posttest value of p=0.002 (p<0.05) there is a change in anxiety in patients with hypertension. Chi-square of blood pressure in the post treatment and control groups p=0.004 (p<0.05) there was a significant change in blood pressure in patients with hypertension in the treatment group. Chi-square of anxiety in the post treatment and control groups p = 0.003 (p<0.05) Benson relaxation combined with murottal Al-Qur'an can reduce blood pressure and anxiety.